Hormonal status monitoring in qualified judokas during trainings - Tuguz, A. R.; Nepso, B. A.; Myzhenya, D. V.; Kagazezheva, N. K.; Kolomiytseva, N. S. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to rate and analyze adaptation of judo elite of the Republic of Adygea to training system based on the serum hormone tests.